2013
DOI: 10.1071/an12301
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, persistence and presence of Synergistes jonesii in cattle grazing leucaena in Queensland: on-farm observations pre- and post-inoculation

Abstract: A study of eight commercial cattle herds grazing leucaena (Leucaena leucocephala subsp. glabrata) pastures was undertaken to determine (1) the efficacy of in vitro Synergistes jonesii inoculum (produced in an anaerobic fermenter) in degrading the dihydroxypyridone (DHP) isomers produced during digestion of leucaena forage; and (2) the persistence of the inoculum in the rumen of cattle following a period grazing non-leucaena pastures. Cattle were introduced to the leucaena pastures for an initial period varying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 29 publications
2
28
1
2
Order By: Relevance
“…Plasma concentration of 2,3-DHP in the SS treatment was higher than reported by Phaikaew et al (2012), who observed that concentrations from 142 to 182 μg/mL in urine are indicative of subclinical toxicity in cows. Given the strong correlation between DHP levels in urine and blood (Graham et al 2013), it is reasonable to suggest that cows in the SS treatment had subclinical toxic levels of 2,3-DHP.…”
Section: Discussionmentioning
confidence: 98%
“…Plasma concentration of 2,3-DHP in the SS treatment was higher than reported by Phaikaew et al (2012), who observed that concentrations from 142 to 182 μg/mL in urine are indicative of subclinical toxicity in cows. Given the strong correlation between DHP levels in urine and blood (Graham et al 2013), it is reasonable to suggest that cows in the SS treatment had subclinical toxic levels of 2,3-DHP.…”
Section: Discussionmentioning
confidence: 98%
“…However, recent findings worldwide have indicated the frequent occurrence of high levels of DHP in animals, which were otherwise considered protected by S. jonesii. Concerns regarding the efficacy of the inoculum were initially raised in 2004, following a survey of Queensland cattle which revealed high DHP levels in urine of animals grazing leucaena (Dalzell et al 2012;Graham et al 2013). Similar findings were subsequently recorded in ruminants in Thailand (Phaikaew et al 2012), Mexico (Contreras-Hernández et al 2013Ruz-Ruiz et al 2013), and Indonesia (Halliday et al 2013;Halliday et al 2014b) (Chapter 4), where animals were often fed high levels of leucaena in diet, up to 100%.…”
Section: List Of Tablesmentioning
confidence: 99%
“…Since their animals fed leucaena may still be performing better than those without legume, there is understandable denial that toxicity is an issue. Another highly anomalous situation is that many ruminants in the tropical world are consuming large amounts of leucaena for prolonged periods and excreting high concentrations of urinary DHP without any apparent clinical symptoms of toxicity (Phaikaew et al 2012;Graham et al 2013;Halliday et al 2014c), including no indication of goitre (Palmer et al 2010). The reasons for this are not understood, but may be due to alternative detoxification pathways such as chemical conjugation of the toxins, discussed later in this review.…”
Section: Confusion Regarding the Symptoms And Molecular Structure Of mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work with repeated inoculation of beef heifers with bison rumen contents altered the rumen microbiome and metabolic activity eliciting increased protein and nitrogen retention on a nutritionally poor straw diet (Ribeiro et al, 2017). Another example is the discovery of Synergistes jonesii in goats which conveys the ability of the host to degrade the otherwise toxic pyridinediol compounds from the fodder plant Leucaena leucocephala, which was successfully conveyed to Australian beef cattle and sheep (Graham et al, 2013). Both of these examples demonstrate the rapid adaption of host to dietary changes acquired through the incorporation of beneficial microbes into the rumen community.…”
Section: Prospective For Using Rumen Microbiota To Obtain Desired Chamentioning
confidence: 99%